Pediatric Differentiated Thyroid Carcinoma: Outcome in Response to Initial Treatment (Bangladesh Journal of Otorhinolaryngology, 2019)
Introduction: Though the differentiated thyroid carcinoma in children is a common pediatric endocrine malignancy, its prognosis is excellent with a proper initial treatment.Objectives: This is to evaluate the initial treatment patern for a good prognosis with longterm outcome in pediatric DTC patients.Methods: This study is a prospective one done in BSMMU during a period of 10 years in 52 post-operative pediatric DTC patients after excluding the follow-up missing patients. These patients are yet in a regular follow-up were outcome evaluated with clinical, pathological & imaging studies.Results: All the patients got initial treatment of total thyroidectomy. About half of the group had undergone neck dissection along with total thyroidectomy. Forty six patients had taken 131-I therapy. The survival is 100%.Conclusion: The life expectancy for children with DTC is excellent. However, many patients experience adverse effects from thyroid surgery, resulting in life long complications. Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 143-148